2000
DOI: 10.1046/j.1365-2184.2000.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle checkpoints and their inactivation in human cancer

Abstract: Checkpoints are mechanisms that regulate progression through the cell cycle insuring that each step takes place only once and in the right sequence. Mutations of checkpoint proteins are frequent in all types of cancer as defects in cell cycle control can lead to genetic instability. This review will focus on three major areas of cell cycle transition control, with particular attention to the alterations found in human cancer. These areas include the G1/S transition, where most cancer-related defects occur, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
261
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(281 citation statements)
references
References 124 publications
6
261
0
8
Order By: Relevance
“…17) The control of cell-cycle progression in cancer cells is considered an effective strategy to prevent or delay tumor growth. 18,19) This assumption is based on a molecular analysis of human cancer, wherein cell cycle regulators are frequently de-regulated in most of the common malignancies. 20,21) Despite recent advancement in understanding the carcinogenic process of PCA, the increasing incidence and relatively low remission rate of chemotherapy have prompted the scientific community to establish more effective treatment regimens by adopting novel and innovative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…17) The control of cell-cycle progression in cancer cells is considered an effective strategy to prevent or delay tumor growth. 18,19) This assumption is based on a molecular analysis of human cancer, wherein cell cycle regulators are frequently de-regulated in most of the common malignancies. 20,21) Despite recent advancement in understanding the carcinogenic process of PCA, the increasing incidence and relatively low remission rate of chemotherapy have prompted the scientific community to establish more effective treatment regimens by adopting novel and innovative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…However, cell cycle arrest at the G2/M checkpoint is a critical component of stress response, allowing DNA damage repair (Kaufmann, 1995;Molinari, 2000;Stark and Taylor, 2006). Moreover, deficiencies in the G2/M phase checkpoint control are often associated with genomic instability and tumorigenesis (Lobrich and Jeggo, 2007).…”
Section: Foxo and The G1/s Phase Transitionmentioning
confidence: 99%
“…Curcumin treatment modulates expression of G2/M cell cycle regulatory proteins DNA damage generally leads to the activation of the ATM/ATR pathway (Molinari, 2000;Abraham, 2001;Lukas et al, 2001;Huang et al, 2008). To further delineate the molecular mechanism of curcumin-mediated G2/M arrest, we determine its effect on the key-signaling proteins of this pathway.…”
Section: Curcumin Causes Dna Damage and Induces Apoptosismentioning
confidence: 99%
“…(Singh and Khar, 2006;Tse et al, 2007). During DNA damage, cells are blocked in G2/M phase to provide time to repair damaged DNA (Molinari, 2000;Abraham, 2001), or lead to apoptotic cell death in case of severe DNA damage . Several studies have indicated that curcumin induces cell cycle arrest and apoptosis in various human cancer cells (Park et al, 2006;Tan et al, 2006;Srivastava et al, 2007;Weir et al, 2007;Lin et al, 2008;Mackenzie et al, 2008;Sun et al, 2008).…”
Section: Curcumin Causes Dna Damage and Induces Apoptosismentioning
confidence: 99%